Manejo agronómico del cultivo de Mamey Cartagena (Mammea americana)”. - Contreras Franco., Ling Miguel (2021)
This document refers to the agronomic management of the culture of Mamey Cartagena (Mammea americana). The conclusions determine that in this bibliographic review it was verified that in other countries, Mamey Cartagena (Mammea americana) can be used adequately for the preparation of pulp, frozen puree, cakes, sweets, jellies, yogurt, ice cream, cake, wine. It can also be preserved and canned in slices. The powder of the seeds is used medicinally to counteract parasitic skin diseases. An aromatic liquor can be obtained from the distillation of flowers and used in digestive problems and research carried out in other countries has generated information that has made it possible to know its taxonomic identification and agronomic characteristics, but there is no information from Ecuador. Among the recommendations are to carry out studies in Mamey Cartagena (Mammea americana) in Ecuador and encourage farmers to their production and marketing, to give added value to the product, as an alternative to improve their economic income.